Analysis of Perceived Value and Social Influence as an Influence of Consumer's Purchase Decision Iphone Users in Semarang City - Ahmad Zakia Nurochim; Noor - Suroija; Sandi - Supaya (Politeknik Negeri Semarang, 2022)
This study aims to determine the effect of Perceived Value and Social Influence towards consumer’s purchase decision of iPhone users. This study uses a quantitative approach. The population in this study are customers who have purchased an iPhone in January – June 2022. The sample used is 100 customers. The sampling technique in this study was to use non-probability Purposive Sampling. Data is collected using a questionnaire that has been tested for validity and reliability. Data analysis techniques used in this research was classical assumption test, multiple linear analysis, coefficient of determination, F-test, and T-test. Data processing is carried out using SPSS version 25. The results of this study indicate that perceived value and social influence have a positive and significant effect on purchase decisions